2013
DOI: 10.1111/trf.12524
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of preemptive donor lymphocyte infusion based on minimal residual disease in acute leukemia patients after allogeneic hematopoietic stem cell transplantation

Abstract: Our results demonstrated the efficacy and safety of pDLI and suggested that pDLI based on MRD monitoring was superior in acute leukemia patients with potential progression compared with salvage DLI administrated in overt relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The number of patients was limited in the MRD group; nevertheless, observation of high effectiveness and low toxicity of DLI in patients with persistent residual disease is well confirmed. [24][25][26] The time of DLI infusion for NA and RIC indications was similar, and showed a small divergence in individual cases in comparison with the application time for MRD and REL indications. In the former case, this time was determined by the approximate course of HSCT and engraftment, whereas, in the latter, such a large dispersion was caused by the variability of disease nature after HSCT.…”
Section: Discussionmentioning
confidence: 94%
“…The number of patients was limited in the MRD group; nevertheless, observation of high effectiveness and low toxicity of DLI in patients with persistent residual disease is well confirmed. [24][25][26] The time of DLI infusion for NA and RIC indications was similar, and showed a small divergence in individual cases in comparison with the application time for MRD and REL indications. In the former case, this time was determined by the approximate course of HSCT and engraftment, whereas, in the latter, such a large dispersion was caused by the variability of disease nature after HSCT.…”
Section: Discussionmentioning
confidence: 94%
“…Various modifications of DLI have been investigated, such as ex vivo activated DLI and earlier introduction of DLI [24][25][26]. A recent report [26] showed that preemptive DLI given when minimal residual disease (MRD) was detected effectively reverted MRD back to remission in all 16 treated patients with acute leukemia and offered long-term survival in 15 of the 16 patients without increasing the risk of GVHD development. Thus, early detection of potential disease progression by detecting MRD and subsequently performing DLI before overt relapse might be a better way to improve the success of HSCT for AML.…”
Section: Discussionmentioning
confidence: 99%
“…[5] DLI as a leukemia control strategy may be particularly effective when employed preemptively upon detection of disease recurrence by minimal residual disease (MRD) but before frank relapse. [6] We report the case of a now 9-year-old female with multiple recurrent T-ALL for whom second haplo-BMT and successive haplo-DLIs are providing persistent (currently 3 years 5 months posttransplant) disease control with minimal side effects and excellent quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced GVL conferred by establishment of a haploidentical graft further makes possible subsequent use of haploidentical donor lymphocyte infusions (haplo‐DLIs) as a disease control strategy with acceptable toxicities . DLI as a leukemia control strategy may be particularly effective when employed preemptively upon detection of disease recurrence by minimal residual disease (MRD) but before frank relapse …”
Section: Introductionmentioning
confidence: 99%